The role of neuromuscular function in sleep apnea pathogenesis and management: A consensus of experts - Mehra, Reena; Schwab, Richard; Kimoff, R. John; Shah, Neomi; Gottlieb, Daniel J.; Patel, Sanjay R.; Ayas, Najib T.; Hanly, Patrick; Sheean, Geoff; Malhotra, Atul (Frontiers in Sleep, 2023)
Study Objectives. Although the importance of upper airway assessment in the consideration of obstructive sleep apnea (OSA) is recognized, there are current limitations in our approach to assessment. Methods. We convened a group of experts in upper airway neuromuscular physiology and anatomy, sleep apnea endophenotypes, novel therapeutics and sleep epidemiology to summarize existing literature and delineate future opportunities to utilize and incorporate innovative and less invasive techniques to assess and manage OSA. Results. Unmet needs in OSA evaluation and diagnostics include identification of upstream prognostic biomarkers of OSA clinical trajectory and need to identify a multi-faceted metric which would provide more informative mechanistic data. Unmet needs in OSA therapeutics and management encompass enhanced phenotyping to predict better tolerance to positive airway pressure therapy and to extend beyond the one-size-fits all approach to treatment for OSA targeting for instance neuromuscular function and upper airway anatomy. If a quantifiable and repeatable metric could be developed, it could facilitate a precision medicine strategy and personalize treatment, including measuring treatment response to interventions including hypoglossal nerve stimulation (HGNS), myofunctional therapy and neuromuscular electrical stimulation. A key area for future investigation is whether observed neuromuscular changes can identify patients at future risk of OSA, facilitating early intervention or prevention strategies. Conclusions. Overall, recognizing the critical contributions of abnormalities of upper airway neuromuscular function to the pathophysiology of OSA, it may be important to find accurate and reproducible neurophysiological assessments to address existing knowledge gaps in OSA assessment and management.